2016
DOI: 10.1016/j.ijcard.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial transplantation of mesenchymal stromal cells for chronic myocardial ischemia and impaired left ventricular function: Results of the MESAMI 1 pilot trial

Abstract: Unique identifier: NCT01076920.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Of the 23 included studies, 11 evaluated AMI ( n = 509 patients) and 12 evaluated IHF ( n = 639 patients) (Table ). Of these studies, eight were RCTs that evaluated AMI ( n = 429 patients) and five were RCTs that evaluated IHF ( n = 472 patients) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 23 included studies, 11 evaluated AMI ( n = 509 patients) and 12 evaluated IHF ( n = 639 patients) (Table ). Of these studies, eight were RCTs that evaluated AMI ( n = 429 patients) and five were RCTs that evaluated IHF ( n = 472 patients) .…”
Section: Resultsmentioning
confidence: 99%
“…Secondary outcomes assessed included safety or efficacy . Of the IHF studies, four studies evaluated safety , four studies evaluated efficacy , and four studies evaluated both as the primary outcome. Secondary outcomes assessed included efficacy or both efficacy and safety .…”
Section: Resultsmentioning
confidence: 99%
“…They also suggested a possible correlation between cell dose and disease severity. Through a longer, 2-year follow-up, the phase 1 pilot study MESAMI revealed similar benefits from intramyocardial MSC injection in patients with chronic ischemic cardiomyopathy, albeit with a smaller sample size of 10 (58). …”
Section: Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 96%
“…Cellular therapy aimed at improving cardiac function and regenerating new myocardium, has been extensively investigated for cardiac repair 3 . Despite numerous preclinical and clinical studies 49 performed to assess the ability of various stem cell populations to improve cardiac function and reduce infarct size, many important issues remain unresolved, and no cell therapy to date has been demonstrated conclusively to be effective. There are significant limitations to cell therapy in terms of cell retention, survival of the engrafted cells, cell differentiation, and integration of transplanted cells with host tissue 10 .…”
Section: Introductionmentioning
confidence: 99%